3rd International Anatomical and Biomedical Scientific Conference (IABS) 2022 - Adam, Siti Khadijah; Yong, Yoke Keong; Mat Taib, Che Norma; Mohd Moklas, Mohamad Aris; Fakurazi, Sharida; Ab. Hamid, Hasiah; Hussain, Mohd Khairi; Mohamad Zainal, Nurul Hayati; Sa'at, Azmah (Life Sciences, Medicine and Biomedicine, 2022)
Department of Human Anatomy, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, partnered with Universitas Brawijaya, Indonesia to host the virtual 3rd International Anatomical and Biomedical Scientific Conference (IABS) 2022 on 22nd – 24th November 2022. With the theme ‘Rejuvenating health sciences towards inclusive and sustainable ecosystem’, this platform is one of the best avenues that cultivates sharing and exchanging scientific endeavours among scientists, clinicians, postgraduate students and academicians involved in the field of anatomy, health sciences and relevant disciplines. The goal of the Special Issue is to revitalise the body of knowledge in health sciences to enhance and offer a sustainable and inclusive ecosystem now that the COVID-19 pandemic has transitioned to the endemic stage globally. Submissions that conceptually, experimentally, or theoretically analyse and explain some of the major problems with achieving the objectives. In light of this, this Special Issue of the conference proceedings aims to integrate practitioner and academic viewpoints. This special issue, in particular, can advance the theory and synthesis of the selected topic. Additionally, it can present fresh findings from experiments, drawing attention to the effectiveness of techniques now employed by subject-matter experts.